Institutions for the Selection of Entrepreneurs: Implications for Economic Growth and Financial Crises - Pavel Pelikan (The Research Institute of Industrial Economics (IUI), 1999)
The search for growth-promoting policies is found to demand knowledge of how growth depends upon actions of entrepreneurs and how these actions depend upon the prevailing institutions. While institutions have extensively been examined for their influences upon the freedoms and the incentives of entrepreneurs, and thereby upon the level of employment of resources, this paper examines their influences upon the selection of entrepreneurs, and thereby upon the efficiency of that employment. This selection is crucial in the realistic but in theory seldom considered cases in which all agents, including entrepreneurs, may differ in economic abilities. A simple model shows that in the long run, selection by market competition, especially when extended to financial markets, vastly outperforms selection controlled or protected politically. Such selection may outperform market selection only during a limited period, extendable only at the price of growing bad debts and financial crises.
Keywords: D90; E44; G10; O10; O40; P51; 330; Eonomic growth; growth-promoting policies; institutions; economic abilities; entrepreneurs; investors; voters; market selection; government selection; financial markets; financial crises; Institutionalismus; Wirtschaftswachstum; Wachstumspolitik; Entrepreneurship-Ansatz; Wettbewerb; Theorie